Ethnomathematics-Based PBL and Mathematical Problem-Solving Ability: A Systematic Literature Review - Simbolon, Novi Tari; Eduard, Eduard; Togatorop, Jainal B.; Wahyuni, Ratna (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2026)
This study aims to synthesize empirical evidence on the implementation of ethnomathematics-based Problem-Based Learning (PBL) in enhancing students' mathematical problem-solving ability and fostering cultural appreciation. A qualitative Systematic Literature Review (SLR) was conducted following the PRISMA 2020 guidelines. An initial search through Google Scholar via Publish or Perish yielded 62 records, of which 15 peer-reviewed empirical studies published between 2021 and 2025 met the inclusion criteria. Data were collected using a structured extraction matrix documenting study characteristics, intervention types, participants, outcome measures, and reported statistical results, then analyzed through thematic qualitative synthesis supported by descriptive aggregation of quantitative indicators including N-Gain scores, effect sizes, and significance testing. Findings reveal consistent positive trends across all included studies. Improvements in mathematical problem-solving outcomes were universally reported, with 27% of studies indicating moderate-to-high N-Gain values and 20% reporting gains in self-efficacy or learning independence. Regarding cultural appreciation, multiple studies documented that ethnomathematics-based PBL heightened students' awareness of local cultural heritage, strengthened cultural identity, and increased engagement with indigenous mathematical practices. These sociocultural outcomes were found to reinforce rather than compete with cognitive gains. Collectively, the findings support a contextual-constructivist framework in which structured inquiry embedded in culturally relevant contexts synergistically develops both mathematical competence and cultural awareness in mathematics education.